Pre-announcement and event-period private information - Kim, Oliver; Verrecchia, Robert E. (Journal of Accounting and Economics, 1997)
Pre-announcement information is private information gathered in anticipation of a public disclosure. Event-period information is private information useful in conjunction with the announcement itself. Typically rational models of trade are based exclusively on one type of information. Such models are less descriptive of real market settings and misspecified empirically. Therefore, we introduce a model of rational trade with both features and discuss its implications.